EVALUASI SISTEM PENGENDALIAN INTERN DALAM MEMINIMALKAN RESIKO KREDIT MACET STUDI KASUS PADA KOPERASI SIMPAN PINJAM AN NISA’ - NIKMATUL L, FARIDA Nikmatul (Jurnal Akuntansi AKUNESA, 2013)
Problems that often occur in financial institutions is stuck klaim, it required asystem to control. The purpose of this research was to evaluate how far theinternal control of credit has influence toward minimize stuck claim. Researchmethod used is descriptive qualitative. The result of this research indicates thatimplementation of the internal control at credit system has an important roletoward credit quality raising and can minimize procentation of stuck claimalthought it still has a few weaknesses.Keyword : internal control, stuck claim, credit